2017
DOI: 10.1101/137901
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Oropharynx as a Distinct Colonization Site forstaphylococcus aureusin the Community

Abstract: Summary line: The oropharynx is an important site for S. aureus colonization in the community.Keywords: Staphylococcus aureus; Methicillin-Resistant Staphylococcus aureus; oropharynx; Nasal Cavity; Cohort Studies . CC-BY-NC-ND 4.0 International license peer-reviewed) is the author/funder. It is made available under a The copyright holder for this preprint (which was not . http://dx.doi.org/10.1101/137901 doi: bioRxiv preprint first posted online May. 15, 2017; 2 ABSTRACT Background: S. aureus is a frequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…These studies noted occurrence rates ranging from 10.5% to 26% (Amala et al, 2015;Onaolapo et al, 2015;Owaku et al, 2018;Abiose 2019;Akinrotoye et al, 2019) but lower than the 56.48% and 66.7% described in a 2017 study(Akinjogunla and Divine-Anthony, 2017). S. aureus in a known commensal carried in the nasopharyngeal region by up to 30% of the human population (Hanson et al,2017). The presence of this organism on door handles could therefore represent poor hygiene practices involving contact of the hand and nose and a lack of proper hand hygiene.…”
Section: Resultsmentioning
confidence: 99%
“…These studies noted occurrence rates ranging from 10.5% to 26% (Amala et al, 2015;Onaolapo et al, 2015;Owaku et al, 2018;Abiose 2019;Akinrotoye et al, 2019) but lower than the 56.48% and 66.7% described in a 2017 study(Akinjogunla and Divine-Anthony, 2017). S. aureus in a known commensal carried in the nasopharyngeal region by up to 30% of the human population (Hanson et al,2017). The presence of this organism on door handles could therefore represent poor hygiene practices involving contact of the hand and nose and a lack of proper hand hygiene.…”
Section: Resultsmentioning
confidence: 99%
“…Colonization of S. aureus in the nose and pharynx is a multifactorial process that involves genetic aspects of the host, virulence factors of the pathogen, and possible interactions between the microbiota of the host [14], although in principle it is thinks that colonization of the pharynx is secondary to colonization of the nose, it is likely that both processes are independent [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the longitudinal study, 12 of the 129 adults were oropharynx only colonizers and 22 were colonized in both the nose and throat. In the longitudinal portion of this study, the throat was again found to be more sensitive than the nose in identifying S. aureus carriers (77.3% vs. 72.7% respectively) [41,42]. In this study, 72 participants (47.4%) were categorized as non-carriers, 49 (32.2%) were categorized as intermittent carriers, and 31 (20.4%) were categorized as persistent carriers [42].…”
Section: Colonization With S Aureusmentioning
confidence: 89%
“…However, this may be due to sampling bias as the number of studies examining the nose as a colonization site far exceeds any other body site. Other body sites known to carry S. aureus are: skin [39], perineum [40], oropharynx [39,[41][42][43][44] gastrointestinal tract [45][46][47], axilla [48], and vagina [39,48] (Figure 2-1 were colonized with S. aureus at baseline in either the nose or throat [42]. Thirty-three of the 79 were colonized only in their throat and 35 in both their nose and throat.…”
Section: Colonization With S Aureusmentioning
confidence: 99%
See 1 more Smart Citation